Theory and evidence of women’s political exclusion in Brazil - Mardegan, Ivan Osmo (2020)
This doctoral dissertation aims to investigate the mechanisms behind female exclusion from Brazilian politics. The study proposes an analytical lens to identify different moments where the exclusion of women from politics occurs, elaborated through an extensive survey of the literature that covers the field in Brazil and other countries. Electoral disputes for the position of Federal Deputy between the years 2006 and 2018 were used as cases for the investigation. Using a quantitative analysis, the study points out that, at the time of the election, there is a deficit of competitive female candidates in proportion to male candidates. This disproportionality may be directly linked to the low proportion of women elected and is mainly the result of the low number of potential competitive female candidates available for party recruitment and of the lower rates of competitiveness and recruitment among married women. Structural inequalities are likely to suppress the supply of competitive female candidates before they are even available for recruitment. Measures that promote greater and better electoral experiences among women and that manage to break with gender stereotypes that determine a sexual division of labor may be fundamental to increase female presence in Brazilian politics.